Decrease in Inpatient Telemetry Utilization Through a System‐Wide Electronic Health Record Change and a Multifaceted Hospitalist Intervention. Issue 8 (9th February 2018) - Edholm, Karli; Kukhareva, Polina; Ciarkowski, Claire; Carr, Jason; Gill, David; Rupp, Austin; Morshedzadeh, Jack; Wanner, Nathan; Kawamoto, Kensaku
Abstract : BACKGROUND: Unnecessary telemetry monitoring contributes to healthcare waste. OBJECTIVE: To evaluate the impact of 2 interventions to reduce telemetry utilization. DESIGN, SETTING, AND PATIENTS: A 2‐group retrospective, observational pre‐ to postintervention study of F35, 871 nonintensive care unit (ICU) patients admitted to 1 academic medical center. INTERVENTION: On the hospitalist service, we implemented a telemetry reduction intervention including education, process change, routine feedback, and a financial incentive between January 2015 and June 2015. In July 2015, a system‐wide change to the telemetry ordering process was introduced. MEASUREMENTS: The primary outcome was telemetry utilization, measured as the percentage of daily room charges for telemetry. Secondary outcomes were mortality, escalation of care, code event rate, and appropriateness of telemetry utilization. Generalized linear models were used to evaluate changes in outcomes while adjusting for patient factors. RESULTS: Among hospitalist service patients, telemetry utilization was reduced by 69% (95% confidence interval [CI], ‐72% to ‐64%; P < .001), whereas on other services the reduction was a less marked 22% (95% CI, ‐27% to ‐16%; P < .001). There were no significant increases in mortality, code event rates, or care escalation, and there was a trend toward improved utilization appropriateness. CONCLUSION: Although electronic telemetry ordering changes can produce decreases in hospital‐wide telemetry monitoring, a multifaceted intervention may lead to an even larger decline in utilization rates. Whether these changes are durable cannot be ascertained from our study.